2019
DOI: 10.1167/iovs.18-24154
|View full text |Cite
|
Sign up to set email alerts
|

Projection-Resolved Optical Coherence Tomography Angiography Parameters to Determine Severity in Diabetic Retinopathy

Abstract: The purpose of this study was to assess projection-resolved optical coherence tomography angiography (PR-OCTA) vessel density (VD) and foveal avascular zone (FAZ) in determining severity within diabetic retinopathy (DR) and their accuracy in identifying highrisk DR patients. METHODS. This was a retrospective study with 72 eyes of 52 DR patients, assessing the VD and FAZ area of the superficial capillary plexus (SCP) and deep vascular plexus (DVP), for both 3 3 3-mm and 6 3 6-mm scans between the DR groups (mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…However, artifacts, particularly projection artifacts, limits the accurate interpretation of DCP vasculature. Despite efforts in resolving the projection artifacts, the projection-resolved OCT-A algorithm still cannot remove the projection artifacts entirely, particularly those from the larger vessels [18][19][20]. For these limitations, our study resorted to enforcing stringent criteria to minimize image artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, artifacts, particularly projection artifacts, limits the accurate interpretation of DCP vasculature. Despite efforts in resolving the projection artifacts, the projection-resolved OCT-A algorithm still cannot remove the projection artifacts entirely, particularly those from the larger vessels [18][19][20]. For these limitations, our study resorted to enforcing stringent criteria to minimize image artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the DCP would mostly be affected in case of hypoxia. Functionally, DCP located in a watershed zone of oxygen supply 36 . The DCP supplies oxygen to the inner retina and the outer retina, while the SCP only needs to maintain the oxygen stability of the inner retina 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rodrigues et al showed that the parafoveal vessel density in the DCP was the parameter that was most closely associated with ETDRS grading [32]. Another study showed that the 3 × 3-mm SCP and the DCP vessel density were the most accurate parameters for the detection of high-risk DR [33]. Using a statistical model, another study identified the superficial capillary plexi of the FAZ area, DCP vessel density, and acircularity as parameters that best distinguished between DR severity groups [34].…”
Section: Octa For Non-proliferative Diabetic Retinopathymentioning
confidence: 99%
“…Projection artefacts occur when more superficial flow signals are projected onto deeper retina layers [87]. One recent study showed that projection-resolved OCTA parameters significantly improved the vascular density analysis of the DCP [33]. Other artefacts include shadow artefacts from larger retinal vessels and artefacts created by fine movement from pigment epithelial defects and fine tissue [3].…”
Section: General Limitations Of Octamentioning
confidence: 99%